MODEL BIMBINGAN DAN KONSELING MULTIKULTURAL UNTUK MENGATASI PERMASALAHAN AKADEMIK DAN SOSIAL MAHASISWA PERGURUAN TINGGI AGAMA ISLAM - YULI NURMALASARI; WIWIED WIDIYANTI (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2018)
Cultural diversity is wealth, opportunities, and challenges. In the world of education, cultural diversity is not always good for students' academic social development. Negative manifestations such a phenomena culture shock, destructed communications, or extra intra-psychic conflicts among students. As an integral part of the education, guidance and counseling has a vital role in developing a counseling model in accordance with that diversity. The method used is research and development. The research sample is determined through the proportional sampling. Results showed that multicultural counseling model effective in addressing the academic and social student Islamic colleges, which is indicated by the results of statistical tests, analysis of counseling journal, anecdotal records, and observation of the behavior of the counselee. Recommendations intended for counseling practitioners in PTAI that helped develop and refine the model in accordance with the needs analysis in the local cultural context; for further research to develop methods, designs, as well as the coverage areas of research.Â